Synthesis and properties of some 3-(5-(4-methoxyphenyl)pyrazol-3-yl)-6-R-[1,2,4]triazolo[3,4-b][1,3,4]thiadiazoles - S. O. Fedotov; A. S. Hotsulia; O. I. Panasenko (Zaporozhye State Medical University, 2022)
Pyrazole and 1,2,4-triazole derivatives play an important strategic role in modern medicine and pharmacy. This fact is due to the significant possibilities of chemical modification and significant pharmacological potential among the derivatives of these heterocycles. The introduction of 1,2,4-triazole and pyrazole fragments into the structure of new substances allows to influence the formation of a certain type of activity. The structural combination of these heterocycles in one molecule increases the likelihood of interaction with various biological targets. At the same time, the creation of condensed systems involving 1,2,4-triazole is undoubtedly scientifically attractive and promising. The aim of the research was to study the conditions for obtaining 3-(5-(4-methoxyphenyl)pyrazol-3-yl)-6-R-[1,2,4]triazolo[3,4-b][1,3,4]thiadiazoles and studying the properties of these compounds. Materials and methods. The first stage of the synthetic part of the work involved the use of diethyl oxalate and 1-(4-methoxyphenyl)ethan-1-one with the participation of sodium hydride in toluene. The obtained ethyl 4-hydroxy-4-(4-methoxyphenyl)-2-oxobut-3-ethanoate in the next step was used in the process of conversion into ethyl 5-(4-methoxyphenyl)pyrazole-3-carboxylate with the participation of hydrazine hydrate. Further modification of the molecule was the stepwise formation of the structure of 4-amino-5-(5-(4-methoxyphenyl)pyrazol-3-yl)-1,2,4-triazole-3-thiol. The next stage of the work involved the interaction with carboxylic acids in the environment of phosphorus oxychloride. To determine the composition and identify the structure of the isolated substances, 1H NMR and infrared spectra were recorded, as well as qualitative and quantitative indicators of the elemental composition of the synthesized structures were obtained. The individual nature of the presence of substances and the degree of their purity were determined using high performance liquid chromatography. Results. Synthesis of 3-(5-(4-methoxyphenyl)pyrazol-3-yl)-6-R-[1,2,4]triazolo[3,4-b][1,3,4]thiadiazoles was performed and optimal conditions were determined the process of obtaining these substances. The structure of the products of chemical transformation was confirmed and the results of the study of physical properties were recorded. The results of docking studies allowed to confirm the prospects of the chosen direction of synthetic transformations, which ultimately allowed to determine the biological potential of the obtained compounds. The model enzyme was 14-α-demethylase lanosterol (code 3LD6), information on which was used from the database of the Protein Structures Database (PDB). Conclusions. As a result of the molecular docking, data were obtained that form an idea of a certain level of probability of the effect of synthesized compounds on the activity of 14α-demethylase lanosterol, which justified the need for further study of antifungal activity.